Computational modelling of the scoliotic spine: A literature review. (21st June 2021) - Gould, Samuele L.; Cristofolini, Luca; Davico, Giorgio; Viceconti, Marco
Abstract: Scoliosis is a deformity of the spine that in severe cases requires surgical treatment. There is still disagreement among clinicians as to what the aim of such treatment is as well as the optimal surgical technique. Numerical models can aid clinical decision‐making by estimating the outcome of a given surgical intervention. This paper provided some background information on the modelling of the healthy spine and a review of the literature on scoliotic spine models, their validation, and their application. An overview of the methods and techniques used to construct scoliotic finite element and multibody models was given as well as the boundary conditions used in the simulations. The current limitations of the models were discussed as well as how such limitations are addressed in non‐scoliotic spine models. Finally, future directions for the numerical modelling of scoliosis were addressed. Abstract : 116 papers were identified which covered the natural and scoliotic spine. This review systematically analyses the recent developments in modelling the scoliotic spine. Methods of modelling the scoliotic and non‐scoliotic spine were discussed, and areas considered in non‐scoliotic spine models but not in scoliotic spine models were identified. The validation and application of scoliotic models were discussed. The current limitations of scoliotic spine models and possible directions for further research are suggested.